Transportation Distribution Analysis to Reduce Carbon Emissions - Kushariyadi, Kushariyadi; Adi, Tri Warcono; Sugito, Bambang; Aristantia, Selvia Eka; Taufiqurrahman, Mohammad Aviciena (Journal of Information System, Technology and Engineering, 2024)
This study aims to investigate the role of PT. TBBM Tanker Car transportation distribution in distributing fuel oil with its tree logic in realizing a green energy system. The primary focus lies in enhancing the efficiency of transportation distribution to facilitate the utilization of green energy through route enhancements. The study underscores the significance of devising efficient transportation distribution routes and advocating for modifications in the quantity and type of tanker car fleets used in its operations. The Saving Matrix Method yielded results from the improvement of the existing Route 17 Routes to 7 Routes, which showed improvements to 10 routes. Consequently, the efficiency of the 17 routes, which provided 17 tanker cars, was improved to 7 routes, indicating a need for 7 tanker cars. A tanker car with a 32 KL capacity operates on Route 1 from gas stations 16, 15, and 14. A tanker car with a 32 KL capacity operates on Route 2 from gas stations 13, 12, and 11. A tanker car with a 32 KL capacity operates on Route 3 from gas stations 10, 9, and 8. Route 4 operates from gas stations 7 and 6, using a tanker car with a capacity of 24 KL; Route 5 operates from gas stations 4 and 3, using a tanker car with a capacity of 24 KL. Route 6 utilizes a 32 KL tanker car from gas stations 2 and 1, while Route 7 utilizes a 24 KL tanker car from gas stations 17. By utilizing only 7 tanks from 17 tankers, we anticipate a significant reduction in carbon emissions, ensuring environmental sustainability.